Perceived Macroeconomic Factors and Stock Market Capitalization: Experience from the Nigerian Economy Perspective - Igoni, Suoye; Ogiri, Itotenaan Henry; Orlu, Lucky (Asian Journal of Economics and Empirical Research, 2020)
The interference of perceived macroeconomic variables on stock market performance despite the continuous management of monetary and fiscal policies has raised eyes brow and motivated for this study. The purpose of this study is to examine the magnitude of relationships of the perceived macroeconomic factors and stock market performance during its interface. Therefore this study evaluated the prevailing interrelationships between Nigerian Stock Market Performance and the Perceived Macroeconomic factors of Exchange rate, External reserves, Gross Domestic Product, Inflation rate and Interest rate. The data information is sourced from Central Bank of Nigeria statistical bulletin between 1985 and 2014. The Augmented Dickey Fuller, Johansen Co-integration, and the Error Correction Models were employed. The results of the ADF revealed that all variables were stationery at first level differences. The results in Johansen Co-integration indicate a significant long run relationship between three studied variables that relate with the Nigeria Stock Market performance. Further, ECM results reported that GDP remains significant variable that respond to stock market performance positively, while inflation responded negatively, while interest rate and external reserves are shown to responding and adjusting to trends in Stock Market Capitalization. And market capitalization and exchange rate are operating independent of each other. The study concluded that GDP and inflation rate constitute the significant policy variables of interest to manage and promote the desired performance of Nigerian stock market. The study recommend for increase of output of goods and services, and adequate management of inflation rate.